Edukasi dan Pendampingan Penerapan Buku Kas Harian bagi UMKM Pasar Perumnas Kota Cirebon - Aan Kanivia; Dewi Anggun Puspitarini; Tiara Maharani; Rhesya Putri Melani; Chaoliyah Rosianah (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2025)
This Community Service Program aims to improve the financial management accountability of MSME traders at the Perumnas Traditional Market, Cirebon City, through the implementation of simple daily cash book recording. The program applied an educational and participatory approach tailored to the characteristics of traditional market MSME actors. The approach was implemented through several stages, including mapping the partners’ initial conditions using questionnaires, socialization on the importance of business financial records, simple accounting training, and assistance in daily transaction recording. The subjects of the program consisted of 24 market traders with diverse business backgrounds and scales. The results indicate a significant change in financial recording behavior, as reflected by a decrease in the percentage of traders who did not record transactions and an increase in the use of daily cash books and other recording media. In addition, traders began to separate business finances from household finances and developed a basic understanding of cash flow control. This program demonstrates that the implementation of simple financial recording through an educational and participatory approach can enhance transparency, accountability, and business sustainability among traditional market MSMEs.